R routines for performing estimation and statistical process control under copula-based time series models. Issue 4 (21st April 2017) - Emura, Takeshi; Long, Ting-Hsuan; Sun, Li-Hsien
ABSTRACT: Modeling serial dependence in time series is an important step in statistical process control. We provide a set of automatic routines useful for simulating and analyzing time series under a copula-based serial dependence. First, we introduce routines that generate time series data under a given copula. Second, we provide fully automated routines for obtaining maximum likelihood estimates for given time series data and then drawing a Shewhart-type control chart. Finally, real data are analyzed for illustration. We make the routines available as "Copula.Markov" package in R.